AN OVERVIEW OF CREATIVITY IN DESIGN AND THE QUESTION OF CREATIVITY - Elif TARLAKAZAN (Fırat University, 2021)
Creativity is the cornerstone of generating new ideas. Creating something new and designing original products while creation is the most important subject of the designing process. If the designer cannot produce authentic designs in the process from the first step to the last, the result cannot go beyond imitation. The value of a specific design is evaluated by its originality and originality is achieved by creating designs that are different from what already exist. Thomas Edison would not have invented the light bulb if he had adopted to the idea of burning candles in the dark like the people of his days. He came up with a creative idea, fulfilling its requirements and eventually invented the light bulb over time. His original invention glorified his name and placed him among the most useful people in human history. The concept of creativity, which forms the basis of originality, is also indispensable in the fields of design arts like graphic, ceramic, sculpture, painting, etc. The first step of the design is to shape it as an original idea. The more distinctive and creative the design is, the more unique it is. The extent of originality of the design makes it more precious. In this context; an ideal design is to create the idea with the best way of expression and with the most accurate elements. Creativity is the most decisive part of the creation process. This research is prepared for the concept of creativity and its importance in the determining factor of design authenticity in all art disciplines.